2014
DOI: 10.1586/17512433.2014.909283
|View full text |Cite
|
Sign up to set email alerts
|

Combination pharmacotherapies for stimulant use disorder: a review of clinical findings and recommendations for future research

Abstract: Despite concerted efforts to identify a pharmacotherapy for managing stimulant use disorders, no widely effective medications have been approved. Innovative strategies are necessary to develop successful pharmacotherapies for stimulant use disorders. This manuscript reviews human laboratory studies and clinical trials to determine whether one such strategy, use of combination pharmacotherapies, holds promise. The extant literature shows that combination pharmacotherapy produced results that were better than pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 77 publications
(215 reference statements)
3
21
0
Order By: Relevance
“…Anker et al (2012) demonstrated that the CocH vector blocked reinstatement of cocaine-seeking in rats given priming doses of cocaine, but it did not prevent reinstatement primed by methamphetamine. Thus, like other therapies for polydrug abusers, the best treatment would be a combination of efficacious pharmacological and behavioral measures aimed at pre-existing drug abuse vulnerabilities (Stoops and Rush, 2014). In the future, the efficacy of the present viral vector-delivered treatment could serve as a prototype for the development of novel longterm interventions against an array of abused drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Anker et al (2012) demonstrated that the CocH vector blocked reinstatement of cocaine-seeking in rats given priming doses of cocaine, but it did not prevent reinstatement primed by methamphetamine. Thus, like other therapies for polydrug abusers, the best treatment would be a combination of efficacious pharmacological and behavioral measures aimed at pre-existing drug abuse vulnerabilities (Stoops and Rush, 2014). In the future, the efficacy of the present viral vector-delivered treatment could serve as a prototype for the development of novel longterm interventions against an array of abused drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Combining medications with modest efficacy could result in greater reductions in stimulant self-administration while reducing the risk of side effects associated with higher doses of the treatment drugs. 8 For example, a series of preclinical experiments demonstrated that combining low doses of two different drugs that each modestly attenuate the abuse-related effects of methamphetamine is an effective strategy to manage stimulant use disorders. 8–9 More specifically, combining low doses of oxazepam and metyrapone that were ineffective when tested alone resulted in reduced cocaine self-administration in rats.…”
Section: Introductionmentioning
confidence: 99%
“…8 For example, a series of preclinical experiments demonstrated that combining low doses of two different drugs that each modestly attenuate the abuse-related effects of methamphetamine is an effective strategy to manage stimulant use disorders. 8–9 More specifically, combining low doses of oxazepam and metyrapone that were ineffective when tested alone resulted in reduced cocaine self-administration in rats. 9 In agreement with the preclinical data, oxazepam-metyrapone combinations were well tolerated and significantly reduced cocaine use in a small clinical trial.…”
Section: Introductionmentioning
confidence: 99%
“…One such strategy is combination treatment, especially with medications that display some efficacy when administered alone (Stoops and Rush, 2014). Naltrexone, a mu opioid receptor antagonist, and bupropion, a dopamine and norepinephrine reuptake inhibitor, are two candidate medications that have been evaluated for managing amphetamine use disorder from preclinical research to clinical trials.…”
Section: Introductionmentioning
confidence: 99%